2018
DOI: 10.1186/s12885-018-4556-6
|View full text |Cite
|
Sign up to set email alerts
|

Induction therapy with paclitaxel and bevacizumab followed by switch maintenance therapy with eribulin in Japanese patients with HER2-negative metastatic breast cancer: a multicenter, collaborative, open-label, phase II clinical study for the SBCCSG 35 investigators

Abstract: BackgroundTo examine the efficacy and safety of induction therapy with paclitaxel and bevacizumab followed by switch maintenance therapy with eribulin (ISMT) in Japanese patients with HER2-negative metastatic breast cancer (MBC).MethodsPatients, who had previously undergone a maximum of 2 regimens of chemotherapy, received 3 cycles of induction therapy with paclitaxel (90 mg/m2 intravenously on days 1, 8, and 15 followed by 1-week drug holiday) and bevacizumab (10 mg/kg intravenously after the completion of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…These included studies on eribulin as a first-or second-line treatment, although direct comparisons are limited by study design differences (e.g. the majority of the studies assessed eribulin safety by adverse events) [9,10,15,16,18,19]. Hence, eribulin was well-tolerated, as shown in previous studies, although ADRs, such as the hematologic events, should be taken into consideration for eribulin administration, regardless of the patients' eribulin treatment line status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These included studies on eribulin as a first-or second-line treatment, although direct comparisons are limited by study design differences (e.g. the majority of the studies assessed eribulin safety by adverse events) [9,10,15,16,18,19]. Hence, eribulin was well-tolerated, as shown in previous studies, although ADRs, such as the hematologic events, should be taken into consideration for eribulin administration, regardless of the patients' eribulin treatment line status.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of eribulin as the first-or secondline treatment was not explored in randomized controlled trials. However, some clinical trials (mainly phase 2) and a realworld study reported the efficacy and safety of eribulin as a first-or second-line treatment [6][7][8][9][10][11][12][13][14][15]. Jacot et al reported the activities of eribulin among metastatic breast cancer patients in a multicenter national observational Epidemiological Strategy and Medical Economic (ESME) program in a realworld setting [14].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a switch maintenance approach, similar to that evaluated in IMELDA, was explored by Japanese investigators. Patients received single-agent eribulin after initial bevacizumab/paclitaxel combination therapy [ 33 ]. Although this approach showed activity (median PFS of 10.7 months), neuropathy was the most common adverse event during eribulin maintenance therapy, somewhat undermining the rationale for switching from paclitaxel to eribulin.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Dutch Breast Cancer Research Group compared intermittent versus continuous first-line treatment with bevacizumab plus paclitaxel; unfortunately, this strategy was not successful to demonstrate the noninferiority of the intermittent regimen to continuous treatment in terms of PFS or OS [22]. Promising results have also been reported in a Japanese phase 2 trial in which patients underwent induction therapy with bevacizumab plus paclitaxel followed by maintenance therapy with eribulin (median PFS: 10.7 months; OS: 20.0 months) [23]. Therefore, previous studies examining maintenance therapy have not yielded consistent results, and thus there is a need to explore a maintenance therapy with an optimal balance of toxicity and efficacy.…”
Section: Maintenance Therapy: Clinical Usefulness Of the Addition Of Capecitabine To Endocrine Therapymentioning
confidence: 99%